The Effect of Convenience, Service Quality, and Information Quality on User Satisfaction of Tomoro Coffee Application - Stifanie, Anggi; Nurhadi, Nurhadi (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the influence of Ease of Use, Service Quality, and Information Quality on User Satisfaction of the Tomoro Coffee Application. The background of this study is based on the importance of user experience in using digital applications as a major factor in increasing customer loyalty and satisfaction. This study uses a quantitative approach with an associative research type. Data were obtained through distributing questionnaires to 100 respondents who are Tomoro Coffee application users and were analyzed using multiple linear regression methods. The results of the study indicate that simultaneously the three independent variables, namely Ease of Use, Service Quality, and Information Quality, have a significant effect on User Satisfaction. Partially, each variable also shows a positive and significant effect. These findings indicate that user experience in accessing the application, the quality of services provided, and the presentation of accurate and relevant information are important factors in shaping the level of satisfaction of Tomoro Coffee application users. This study provides implications for application developers to focus more on improving user-friendly features, the quality of digital services, and the reliability of information to increase customer satisfaction.